Pembangunan Terintegrasi dalam Mewujudkan Kota Pariwisata Bertaraf Internasional: Studi Kasus di Kabupaten Banyuwangi Jawa Timur - Bayu Mitra Adhyatma Kusuma (Universitas Muhammadiyah Sidoarjo, 2014)
This study aims to analyze and describe how the integrated development in realizing Banyuwangi as an international tourism city is. The type of research used in this study is a qualitative with analysis descriptive approach. The results of study show that in realizing Banyuwangi as an international tourism city through integrated development, the lokal government of Banyuwangi Regency performs three steps of consolidation, namely improvement of infrastructure for access to the leading tourist destinations, consolidation of lokal cultural wealth, and consolidation of the tourism community. Through such measures, the number of foreign tourist arrivals has increased very significantly from year to year and Banyuwangi received several awards for the accomplishments and contributions in the tourism sector.